Coordination in human and primate groups - Boos, Margarete; Boos, Margarete; Kolbe, Michaela; Kappeler, Peter M.; Ellwart, Thomas; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Coordination in Human and Primate Groups presents one of the first collections of the different approaches and methods used to assess coordination processes in groups. Written by psychologists and primatologists, the book represents a broad range of coordination research fields such as social psychology, work and organizational psychology, medicine, primatology, and behavioural ecology. It is designed for researchers and practitioners interested in understanding the behavioural aspects of group coordination.
Part I Theoretical Approaches to Group Coordination -- Coordination in Human and Nonhuman Primate Groups: Why Compare and How? -- An Inclusive Model of Group Coordination -- Coordination of Group Movements in Nonhuman Primates -- Dimensions of Group Coordination: Applicability Test of the Coordination Mechanism Circumplex Model -- The Role of Coordination in Preventing Harm in Healthcare Groups: Research Examples from Anesthesia and an Integrated Model of Coordination for Action Teams in Health Care -- Developing Observational Categories for Group Process Research Based on Task and Coordination Requirement Analysis: Examples from Research on Medical Emergency-Driven Teams -- Part II Assessing Coordination in Human Groups: Concepts and Methods Part -- Assessing Coordination in Human Groups: Concepts and Methods -- Measurement of Team Knowledge in the Field: Methodological Advantages and Limitations -- An Observation-Based Method for Measuring the Sharedness of Mental Models in Teams -- Effective Coordination in Human Group Decision Making: MICRO-CO: A Micro-analytical Taxonomy for Analyzing Explicit Coordination Mechanisms in Decision-Making Groups -- Part III Primatological Approaches to the Conceptualisation and Measurement of Group Coordination -- Primatological Approaches to the Study of Group Coordination -- Communicative and Cognitive Underpinnings of Animal Group Movement -- Communicative Cues Among and Between Human and Nonhuman Primates: Attending to Specificity in Triadic Gestural Interactions -- Coordination in Primate Mixed-Species Groups.
Electronic reproduction.
Keywords: Group decision making; Cooperativeness; Animal behavior; Electronic books